Anterolateral Ligament Reconstruction Improves Anteroposterior Stability As Well As Rotational Stability in Revision Anterior Cruciate Ligament Reconstruction with High-Grade Pivot Shift - Yoon, Kyoung Ho; Hwang, In Uk; Kim, Eung Ju; Kwon, Yoo Beom; Kim, Sang-Gyun (The Journal of Knee Surgery, 2020)
This study aimed to investigate the effect of anterolateral ligament reconstruction (ALLR) in revision anterior cruciate ligament reconstruction (ACLR) with high-grade pivot shift. The hypothesis was that revision ACLR combined with ALLR (RACLR with ALLR group) would show superior clinical outcomes to those of isolated revision ACLR. We retrospectively evaluated consecutive patients who underwent revision ACLR (RACLR) combined with ALLR between October 2015 and January 2017. The indication for combination of ALLR with revision ACLR was failed ACLR with ≥G2 pivot-shift instability. The control group included patients who underwent isolated revision ACLR (isolated RACLR group) for the same indication between July 2013 and September 2015. Exclusion criteria were ≤G1 pivot-shift instability, multiple ligament reconstruction, bilateral ligament injury, double-bundle reconstruction, insufficient medical records, postoperative infection, and follow-up loss at postoperative 2 years. Clinical scores, stability tests, and failure rates were compared between groups at the 2-year follow-up. The RACLR with ALLR group had 18 patients (mean age, 32.9 ± 10.8 years) and the RACLR group had 21 patients (mean age, 29.6 ± 10.2 years). Clinical scores at the 2-year follow-up showed no significant differences between groups. However, the RACLR with ALLR group showed better stability in the Lachman test (p = 0.005), pivot-shift test (p = 0.030), and side-to-side difference in stress radiographs (3.9 ± 3.0 mm vs. 5.9 ± 2.8 mm, p = 0.018) than the isolated RACLR group. The RACLR with ALLR group had two failures (11.1%), and the RACLR group had three failures (14.3%). In conclusion, ALLR in revision ACLR with high-grade pivot shift improves anteroposterior stability as well as rotational stability at 2-year follow-up. Therefore, ALLR is recommended with revision ACLR, especially in patients with high-grade pivot shift. This is a Level III, retrospective cohort review.
Keywords: anterior cruciate ligament reconstruction; posterior tibial slope; anterolateral ligament reconstruction; clinical outcome; stability